Autonomous shuttles for collective transport: a worldwide benchmark. (22nd February 2021) - Antonialli, Fabio
The present study aimed at performing a comprehensive benchmark on experimentations with autonomous shuttles for collective transport. Data was collected online on both academic and grey literature yielding a research corpus of 176 experimentations. Results show a European lead on both the number of experimentations and manufacturers. The majority of the deployments were aimed towards public transportation being short to mid-term trials, mainly offered free of charge to users. Regular-line transport was the prevailing operational mode adopted, meanwhile, on-demand services were present but incipient, mainly due to legal barriers as well as technological and infrastructural constraints. Eight main typologies of uses able to fulfil both private and public transport offerings were identified, being either focused on solving first- and last-mile issues or microtransit commute. At last, the main common stakeholders were identified, as well as how different forms of value are created and distributed among them.